Bone metabolism and bone mineral density in premenopausal women with mild depression - Kavuncu, V; Kuloglu, M; Kaya, A; Sahin, S; Atmaca, M; Firidin, B (Yonsei Univ College Medicine, 2002)
This study was undertaken to investigate the bone metabolism and bone mineral density (BMD) in female patients suffering from depression. Forty-two female patients diagnosed with depression and 42 healthy women, all in the premenopausal age, were enrolled. A clinical evaluation, measurements of the biochemical markers of bone metabolism and BMD measurements were performed, The BMD values were found to be similar in all measured sites. It was concluded that a low BMD was not a prominent feature of premenopausal women with mild depression, even though an increase in bone resorption was found.
Keywords: depression; bone density; bone metabolis